Implementasi Budaya Organisasi Tats Dalam Peningkatan Efektivitas Layanan Ujian Negara Amatir Radio - Paat, Johny Christofel; Sudarsono, Sudarsono; Muhammad, Ikram (Gorontalo Management Research, 2025)
This study explores the implementation of the organizational culture “Total Action – Total Solution (TATS)” as an instrument to improve the effectiveness and efficiency of public services, with a focus on the Amateur Radio Examination (UNAR) at Loka Monitor SFR Gorontalo. The study aims to (1) describe the stages and mechanisms of TATS implementation, (2) identify supporting and inhibiting factors in its application, and (3) analyze the relationship between TATS and the improvement of UNAR service performance. Using a qualitative descriptive method, data were collected through interviews, documentation, and observation, and analyzed thematically. The results show that TATS has been internalized by employees and translated into actions emphasizing speed, accuracy, transparency, and accountability. Supporting factors include leadership commitment, digital technology adoption, and teamwork, while challenges remain in terms of limited human resources, network instability, and participants’ digital literacy. The implementation of TATS has proven to increase service quality, particularly in responsiveness, reliability, and user satisfaction. This research contributes to the discourse on public sector organizational culture by demonstrating how cultural values can be institutionalized through regulation and practice to strengthen good governance